2015
DOI: 10.1208/s12248-015-9725-9
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: Population Pharmacokinetics and Exposure-Uric Acid Analyses After Single and Multiple Doses of ABT-639, a Calcium Channel Blocker, in Healthy Volunteers

Abstract: The PDF version of the published article contains errors throughout the text, which were introduced by the typesetter when performing the author's proof corrections. This erratum contains the corrected PDF.The online version of the original article can be found at http:// dx.doi.org/10.1208/s12248-014-9709-1. Abstract. ABT-639 is a selective T-type calcium channel blocker with efficacy in a wide range of preclinical models of nociceptive and neuropathic pain. In the current first-in-human (FIH) study, the phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
(10 reference statements)
1
6
0
Order By: Relevance
“…These observations indicate that steady-state concentrations were within the concentration range observed in the phase 1 study for the same dose. 1 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These observations indicate that steady-state concentrations were within the concentration range observed in the phase 1 study for the same dose. 1 …”
Section: Resultsmentioning
confidence: 99%
“…This is particularly noteworthy given that the tolerability and safety profile from a phase 1 study and the current trial was benign and there were no significant safety issues identified. 1 However, based on the findings from animal toxicology studies, 4 it was determined that 100-mg twice daily ABT-639 was the appropriate highest dose with an adequate safety margin for this proof-of-concept study. In addition, the dose used in this study was predicted to provide an exposure level above what was required for efficacy in humans based on the projection from preclinical animal models.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations